Effect of relative velocity between rough surfaces: hydrodynamic lubrication of rotary lip seal - Lahjouji, Imane; El Gadari, Mhammed; El Fahime, B.E.; Radouani, Mohamed (Zielona Góra: Uniwersytet Zielonogórski)
Since the sixties, most of numerical studies that model the rotary lip seal lubrication have been restricted by assuming that one of the two opposing surfaces is smooth: either the lip or the shaft. This hypothesis, although it is verified only for a shaft roughness ten times smaller than that of the seal, is the best solution to avoid the transient term in the deterministic approach. Thus, the subject of the present study is twofold.
Keywords: hydrodynamic lubrication; roughness; relative velocity; Reynolds equation; finite differences